Determination of Cutoff Time and Optimal Length of Border Irrigation with Closed-Ended - Adel Sargolzaei; Mohammad Mahdi Chari; Masoomeh Delbari; Peyman Afrasiab (محیط زیست و مهندسی آب, 2021)
The proper combination of cutoff time and lengths of border are among the criteria for high efficiency in surface irrigation. The objective of this study was to determine cutoff time and the optimal distance and flowrate in closed-ended border systems. The basic assumption in this method is that the point along the field, where the lowest water depth permeates should receive water equal to the required depth. For this purpose, the data applied were consisted of 18 vegetated and non-vegetated borders, and bed slope of 0.001 to 0.005, Maning's roughness of 0.017-0.211, border length of 100 m and flow rate range from 0.08 to 0.16 m3/min.m. After determining the cut-off time, the application efficiency obtained using the method presented in this study was compared with zero inertia (WinSRFR 4.1) model. The highest similarity of results was observed in closed end border for R-6, R-13, R-14 and R-17 border with 0% difference and the highest difference was for R-1 border with 8.67% difference in efficiency. Maximum efficiency was obtained in some border with decreasing length and in some border with increasing length. Generally, it can be concluded that the application efficiency obtained from both methods was close to each other.